Methods of Rendering Vast Landscapes in Simulation Training Systems - Giatsintov, Alexander M.; Reshetnikov , Valery N.; Roditelev, Alexander V. (Computer Tools in Education, 2019)
One of the tasks that arise during the development of training (simulation) systems is the creation of a subsystem for displaying the earth’s surface. Subsystems of this class provide modeling and visualization of the landscape, underlying surface (rivers, roads, forests, etc.), geometric objects that simulate cities or airports and so on. There are two main approaches to the visualization of extended landscapes — continuous level of detail algorithms that use clustered triangulation and geometry clipmapbased algorithms. The method of generation and visualization of the Earth’s surface presented in the work is based on the second approach. It is possible to perform calculations on the GPU using single precision, which allows faster calculations compared to using data types with double precision. In addition, this approach may be used on mobile graphics processors that do not support double precision. The proposed new method of dynamic resource management reduces the occupied video memory, which allows more detailed texture data to be loaded for a larger number of objects simultaneously.